2020
DOI: 10.1093/narcan/zcaa033
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3 enzymes mediate efficacy of cisplatin and are epistatic with base excision repair and mismatch repair in platinum response

Abstract: Identifying the mechanisms mediating cisplatin response is essential for improving patient response. Previous research has identified base excision repair (BER) and mismatch repair (MMR) activity in sensitizing cells to cisplatin. Cisplatin forms DNA adducts including interstrand cross-links (ICLs) that distort the DNA helix, forcing adjacent cytosines to become extrahelical. These extrahelical cytosines provide a substrate for cytosine deaminases. Herein, we show that APOBEC3 (A3) enzymes are capable of deami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Most A3 proteins are found throughout the cell (19) and all A3s except A3A have been previously associated with ribonucleoprotein complexes in the cytoplasm, which is consistent with our PPI dataset (14, 5154). Additionally, although A3D and A3G were thought to be only cytoplasmic, several more recent reports have shown that they are also found in the nucleus (46, 55, 56). Only A3B has a nuclear localization signal that places the majority of A3B in a single compartment, but similar to other A3s, there are conditions where it becomes relocalized to the cytoplasm (53, 57).…”
Section: Resultsmentioning
confidence: 99%
“…Most A3 proteins are found throughout the cell (19) and all A3s except A3A have been previously associated with ribonucleoprotein complexes in the cytoplasm, which is consistent with our PPI dataset (14, 5154). Additionally, although A3D and A3G were thought to be only cytoplasmic, several more recent reports have shown that they are also found in the nucleus (46, 55, 56). Only A3B has a nuclear localization signal that places the majority of A3B in a single compartment, but similar to other A3s, there are conditions where it becomes relocalized to the cytoplasm (53, 57).…”
Section: Resultsmentioning
confidence: 99%
“…This notion is supported by: (a) in vitro experiments showing that in the presence of A3G, Klenow fragment DNA polymerase accomplishes the synthesis of both DNA strands containing minimal homology of two bases [39,61]; (b) A3G undergoes intersegmental transfer [56,62], allowing it to directly juxtapose two ssDNA termini with minimal terminal microhomology leading to error‐free NHEJ and if juxtaposes along the resected ssDNA it will generate error prone‐NHEJ. Others and we showed that A3G, albeit its predominant cytoplasmic protein, can translocate, reside and act in the nuclei [25,39,45,63–66] pointing at its potential to interact with damaged DNA in the cell genome.…”
Section: Discussionmentioning
confidence: 96%
“…Bladder cancer is often treated with the DNA alkylating agent cisplatin, which may have enhanced activity in the presence of APOBEC3s. Mechanistically, APOBEC3s may mediate cisplatin response by deaminating drug-induced extrahelical cytosines, and APOBEC3B may induce further genotoxic effects during chemotherapy-induced mismatch repair [ 188 ]. Additionally, APOBEC3s may generate a high background mutation load that sensitizes cells to additional cisplatin-induced DNA damage.…”
Section: Clinical and Therapeutic Significance Of Apobec3s In Cancersmentioning
confidence: 99%
“…For example, APOBEC3 inducers could prime tumors to respond to platinum-based chemotherapies and DDR inhibitors. As a proof of concept, an in vitro breast cancer study found that inducing APOBEC3s in cell lines with low baseline expression significantly increased responsiveness to cisplatin [ 188 ]. Overexpression of APOBEC3s was also shown to increase responsiveness to targeted ATR and Chk1/2 inhibitors in acute myeloid leukemia and osteosarcoma cell lines [ 52 , 191 ].…”
Section: Clinical and Therapeutic Significance Of Apobec3s In Cancersmentioning
confidence: 99%
See 1 more Smart Citation